Movie and music preferences influencing students’ cultural knowledge in the Yorùbá society - Akinsola, Ifeoluwa Theophilus (Journal of Social, Humanity, and Education, 2025)
Purpose: This study examined how Yorùbá and Non-Yorùbá movie and music preferences correlated with secondary students’ knowledge of Yorùbá cultural concepts in Ibadan, a metropolitan Yoruba society. Research methodology: The study adopted a correlational survey research design. Randomly selected 350 SS II students in Ibadan filled the Students’ Questionnaire on Movie Preferences (r=.93); Students’ Questionnaire on Music Preferences (r=.91); and Yorùbá Cultural Concepts Knowledge Test (r=.81) self-designed for data collection. Data were analyzed using Pearson’s Product Moment Correlation and Multiple Regression Analysis at p<0.05. Results: Findings revealed that knowledge of Yorùbá cultural concepts had a positive correlation with students’ preferences for Yorùbá movie (r = .575; p<.05) and music (r = .564; p<.05) but a negative correlation with students’ preferences for non-Yorùbá movie (r = -.551; p<.05) and music (r = -.485; p<.05). The composite contribution of the independent variables was significant (F (4, 345) = 56.201, p<.05).  Preference for Yorùbá music (?= .227) had the highest relative contribution. Conclusions: Preferences for Yorùbá movie and music are important in improving students’ knowledge of Yorùbá cultural concepts. Limitations: The study was limited to Yoruba and non-Yoruba movies and music, and Yoruba indigenes taking Yoruba as a subject in secondary schools in Ibadan, Nigeria. Future studies should focus on other media products and their influence on cultural knowledge in other Nigerian societies. Contribution: This study established that indigenous music can increase students’ cultural knowledge. This has practical implications for the use of music in indigenous languages and cultural teaching in secondary schools. Therefore, Secondary school students should be encouraged to regularly listen to traditional Yorùbá music and watch Yorùbá movies on all available media, while teachers also utilize them in teaching.